PATHOMORPHOLOGICAL DIAGNOSIS OF SEPTIC DISEASES - Kuliev B.; S.Akhmedov (TADQIQOTLAR, 2025)
Abstract: This article describes the pathomorphological diagnosis of colibacteriosis, salmonellosis and pasteurellosis in farm animals. The purpose of this topic is to create and introduce a local drug (vaccine) to prevent and fight against these diseases.